An Absence of Cutaneous Neurofibromas Associated with a 3-bp Inframe Deletion in Exon 17 of the NF1 Gene (c.2970-2972 delAAT): Evidence of a Clinically Significant NF1 Genotype-Phenotype Correlation - Upadhyaya, M.; Huson, S.M.; Davies, M.; Thomas, N.; Chuzhanova, N.; Giovannini, S.; Evans, D.G.; Howard, E.; Kerr, B.; Griffiths, S.; Consoli, C.; Side, L.; et al. (American journal of human genetics, 2007)
Neurofibromatosis type 1 (NF1) is characterized by café-au-lait spots, skinfold freckling, and cutaneous neurofibromas. No obvious relationships between small mutations (<20 bp) of the NF1 gene and a specific phenotype have previously been demonstrated, which suggests that interaction with either unlinked modifying genes and/or the normal NF1 allele may be involved in the development of the particular clinical features associated with NF1. We identified 21 unrelated probands with NF1 (14 familial and 7 sporadic cases) who were all found to have the same c.2970-2972 delAAT (p.990delM) mutation but no cutaneous neurofibromas or clinically obvious plexiform neurofibromas. Molecular analysis identified the same 3-bp inframe deletion (c.2970-2972 delAAT) in exon 17 of the NF1 gene in all affected subjects. The ΔAAT mutation is predicted to result in the loss of one of two adjacent methionines (codon 991 or 992) (ΔMet991), in conjunction with silent ACA→ACG change of codon 990. These two methionine residues are located in a highly conserved region of neurofibromin and are expected, therefore, to have a functional role in the protein. Our data represent results from the first study to correlate a specific small mutation of the NF1 gene to the expression of a particular clinical phenotype. The biological mechanism that relates this specific mutation to the suppression of cutaneous neurofibroma development is unknown.